Feminisasi Kepemimpinan atau Politik Elit? Analisis Gender terhadap Kepemimpinan Sherly Tjoanda dalam Pembangunan Ekonomi Maluku Utara - Ananda Chanaya Meutya Lestari; Ananda Khansa Sayidina; Ika Arinia Indriyani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
analyzes the leadership of Sherly Tjoanda in regional economic development in Maluku Utara using the Feminist Political Economy perspective. In recent years, North Maluku has experienced significant economic growth driven by the expansion of the nickel industry and mineral downstreaming policies. The dominance of the mining sector has made extractive industries the main driver of the regional economy, but it has also created several challenges, including economic dependence on extractive sectors, potential social inequality, and unequal access to development benefits. A gender perspective is important to understand how power relations, networks of political and economic elites, and economic structures influence development policy-making. The Feminist Political Economy perspective emphasizes that the presence of women in leadership positions does not automatically produce gender transformation within political and economic systems. Therefore, economic development should be analyzed not only in terms of economic growth but also in terms of how development benefits are distributed among different social groups, including women and local communities.   Keywords: Women’s leadership, economic development, nickel industry, North Maluku   Abstrak. Analisis kepemimpinan Sherly Tjoanda dalam pembangunan ekonomi di Maluku Utara dengan menggunakan perspektif Feminist Political Economy. Pertumbuhan ekonomi Maluku Utara dalam beberapa tahun terakhir menunjukkan peningkatan yang sangat signifikan yang didorong oleh ekspansi industri nikel serta kebijakan hilirisasi mineral. Dominasi sektor pertambangan menjadikan industri ekstraktif sebagai penggerak utama perekonomian daerah, namun juga menimbulkan berbagai tantangan seperti ketergantungan ekonomi terhadap sektor ekstraktif, potensi ketimpangan sosial, serta perbedaan akses terhadap manfaat pembangunan. Analisis gender menjadi penting untuk melihat bagaimana relasi kekuasaan, jaringan elit politik dan ekonomi, serta struktur ekonomi memengaruhi proses pengambilan kebijakan pembangunan. Perspektif Feminist Political Economy menekankan bahwa keberadaan perempuan dalam posisi kepemimpinan tidak selalu secara otomatis menghasilkan transformasi gender dalam sistem politik dan ekonomi. Oleh karena itu, pembangunan ekonomi perlu dianalisis tidak hanya dari sisi pertumbuhan ekonomi, tetapi juga dari distribusi manfaat pembangunan bagi berbagai kelompok sosial, termasuk perempuan dan masyarakat lokal.